2000
DOI: 10.1364/ao.39.000887
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric correction algorithm for hyperspectral remote sensing of ocean color from space

Abstract: Existing atmospheric correction algorithms for multichannel remote sensing of ocean color from space were designed for retrieving water-leaving radiances in the visible over clear deep ocean areas and cannot easily be modified for retrievals over turbid coastal waters. We have developed an atmospheric correction algorithm for hyperspectral remote sensing of ocean color with the near-future Coastal Ocean Imaging Spectrometer. The algorithm uses lookup tables generated with a vector radiative transfer code. Aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
138
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(145 citation statements)
references
References 22 publications
1
138
0
Order By: Relevance
“…The majority of the signal reaching a space-borne sensor is actually from sunlight scattered within the atmosphere and reflection off the sea surface that must be removed through the process of "atmospheric correction." Uncertainties in HICO radiometric calibrations prevent the retrieval of aerosol models and optical depths from HICO data on a pixel-by-pixel basis using the ocean version of the atmospheric correction algorithm (36). Instead, a land version is used (37) in the present processing of the HICO imagery.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the signal reaching a space-borne sensor is actually from sunlight scattered within the atmosphere and reflection off the sea surface that must be removed through the process of "atmospheric correction." Uncertainties in HICO radiometric calibrations prevent the retrieval of aerosol models and optical depths from HICO data on a pixel-by-pixel basis using the ocean version of the atmospheric correction algorithm (36). Instead, a land version is used (37) in the present processing of the HICO imagery.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperspectral and fine spectral resolution multispectral sensors allow for the quantitative analysis of spectral features of the canopy biophysical variables (e.g., biomass, water, nitrogen and chlorophyll content, and photosynthesis pigment activity) to be carried out [42][43][44]. The main limitation is that these sensors are usually configured for just one specific index and therefore flexibility to calculate other indices is limited.…”
Section: Radiometric and Spectral Resolutionmentioning
confidence: 99%
“…In this context, many authors (IOCCG, 2010;Gao et al, 2000) demonstrated the crucial role of the aerosol in atmospheric radiative transfer modelling and, consequently, on the accuracy of the results of mainly large-scale atmospheric correction of multi-and hyperspectral remote sensing data.…”
Section: Introductionmentioning
confidence: 99%